2019
DOI: 10.3390/jrfm12010041
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Entrepreneurial Strategy, Network Ties, Human and Financial Capital in New Venture Performance

Abstract: In the current era of globalization and competitive edge, the survival of newly established ventures has become a big challenge. Numerous studies have been carried out to discover factors that are essential for newly initiated ventures but the results are still fragmented. This study focuses on measuring the effect of entrepreneurial strategy, network ties, human capital and financial capital on new venture performance. A structured questionnaire was used to collect data from 196 registered firms located in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(52 citation statements)
references
References 60 publications
(69 reference statements)
2
32
0
Order By: Relevance
“…Accordingly, it is evident that the poor access to finance of SMEs in the emerging markets contributes to poor performance and to their high failure rate. Hence, our findings are consistent with those of Irwin and Scott [43] and Khan et al [44], who concluded that access to finance was a major barrier to the sustainability of SMEs.…”
Section: Discussion Of the Findingssupporting
confidence: 93%
See 1 more Smart Citation
“…Accordingly, it is evident that the poor access to finance of SMEs in the emerging markets contributes to poor performance and to their high failure rate. Hence, our findings are consistent with those of Irwin and Scott [43] and Khan et al [44], who concluded that access to finance was a major barrier to the sustainability of SMEs.…”
Section: Discussion Of the Findingssupporting
confidence: 93%
“…There is a flourishing strand of research dealing with the financial constraints that SMEs encounter [40][41][42]. Access to finance has been identified as one of the major constraints on the sustainability of SMEs [43,44]. Gambetta et al [45] showed that the underdeveloped financial markets and weak financial instruments in emerging economies led to poor allocation of financial sources among business organizations.…”
Section: Access To Finance and Smes' Sustainabilitymentioning
confidence: 99%
“…In developing markets such as Pakistan, sufficient financial capital and resources configure firms to expand their business operations successfully (Degong, Ullah, Khattak, & Anwar, 2018). A recent study conducted by Khan, Li, Safdar, and Khan (2019) demonstrates that entrepreneurial financial capital significantly and positively contributes to new venture performance. They further suggested that the newly established ventures should focus initially to establish relationships with external financial ties and increase their networks to acquire adequate financial capital for their survival and growth.…”
Section: Ef and Nvsmentioning
confidence: 99%
“…Khan et al (2019) collected the data from 196 respondents located in different parts of Pakistan and confirmed the positive impact of entrepreneurial strategies and network ties on venture performance (Khan et al, 2019). Khan et al (2019) further recommended that entrepreneurs should develop effective business strategies and inflate their business network to grasp useful and innovative resources and enhance their FFP. Thus, regarding Chinese (C) and Pakistani (P) entrepreneurs, this study proposes the following:…”
Section: Factors Of Social Competence and Ffpmentioning
confidence: 93%
“…Shu et al (2019) conducted a study on 230 China-based firms and concluded that entrepreneurial orientation and strategic renewal with the support of state institutions significantly impacts firm financial and non-financial performance (Shu et al, 2019). Khan et al (2019) collected the data from 196 respondents located in different parts of Pakistan and confirmed the positive impact of entrepreneurial strategies and network ties on venture performance (Khan et al, 2019). Khan et al (2019) further recommended that entrepreneurs should develop effective business strategies and inflate their business network to grasp useful and innovative resources and enhance their FFP.…”
Section: Factors Of Social Competence and Ffpmentioning
confidence: 99%